The relationship between refractive error and the risk of diabetic retinopathy: a systematic review and meta-analysis - Li, Yanqing; Hu, Pengcheng; Li, Li; Wu, Xianhui; Wang, Xi; Peng, Yanli (Frontiers in Medicine, 2024)
Purpose: This meta-analysis was conducted to collect all available data and estimate the relationship between refractive error and the risk of diabetic retinopathy (DR) in patients with diabetes, and to assess whether vision-threatening DR (VTDR) is associated with refractive error.We systematically searched several literature databases including PubMed, Embase, Cochrane Library, Web of Science, CNKI, CBM, Wan Fang Data, and VIP databases. Pooled odds ratios (OR) and 95% confidence intervals (CI) were calculated using fixed or random effects models.Four models were developed to assess the relationship between refractive error and the risk and DR, VTDR: hyperopia and DR, VTDR; myopia and DR, VTDR; spherical equivalent (SE per D increase) and DR, VTDR; and axial length (AL per mm increase) and DR, VTDR. The included literature was meta-analyzed using Stata 12.0 software, and sensitivity analysis was performed. Publication bias in the literature was evaluated using a funnel plot, Begg's test, and Egger's test.A systematic search identified 3198 articles, of which 21 (4 cohorts, 17 cross-sectional studies) were included in the meta-analysis. Meta-analysis showed that hyperopia was associated with an increased risk of VTDR (OR ： 1.23 ； 95% CI ： 1.08-1.39 ； P=0.001), but not with DR (OR ： 1.05 ； 95% CI： 0.94-1.17 ； P=0.374). Myopia was associated with a reduced risk of DR (OR ： 0.74 ； 95% CI： 0.61-0.90 ； P=0.003), but not with VTDR (OR ： 1.08；95% CI：0.85-1.38； P=0.519). Every 1 diopter increase in spherical equivalent, there was a 1.08 increase in the odds ratio of DR (OR：1.08；95% CI：1.05-1.10； P＜0.001), but not with VTDR (OR：1.05； 95% CI：1.00-1.10； P=0.06). AL per mm increase was significantly associated with a decreased risk of developing DR (OR：0.77；95% CI：0.71-0.84； P＜0.001) and VTDR (OR：0.63；95% CI：0.56-0.72； P＜0.001). Analysis of sensitivity confirmed the reliability of the study's findings.This meta-analysis demonstrates hyperopia was associated with an increased risk of VTDR in diabetes patients. Myopia was associated with a reduced risk of DR. AL is an important influencing factor of refractive error. Every 1mm increase in AL reduces the risk of DR by 23% and the risk of VTDR by 37%.